A plant pathogen causes extensive mortality in an invasive insect herbivore. (13th May 2015) - Graziosi, Ignazio; Rieske, Lynne K.
Abstract We investigate a plant–microbe–insect interaction where a plant pathogenic microorganism is utilizing an invasive insect herbivore as an alternate resource, and test the hypothesis that the microorganism is affecting the population dynamics of the herbivore on its woody host plant. We investigated the presence of necrotic lesions formed by an unknown microbe on galls induced by the Asian chestnut gall wasp Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae), a global pest on Castanea hosts. We hypothesize that colonization by this plant‐associated microbe impacts survival and invasiveness of the gallmaker and, using Koch's postulates, we evaluate its effects on the gallmaker and on the gallmaker's primary natural enemy. Morphologically identical colonies were isolated from galls and insects, and DNA sequences matched with the fungal genus Colletotrichum, a causal agent of plant‐pathogenic anthracnose. Inoculations generated comparable symptoms. After the formation of superficial lesions, the pathogen rapidly penetrates galls, colonizing insect tissue in gall chambers and causing extensive larval mortality. Minimal effects were evident on the associated parasitoid Torymus sinensis Kamijo (Hymenoptera: Torymidae). We report a plant pathogen utilizing a gall‐inducing arthropod at the same time as sparing its parasite and expand reports of Colletotrichum impacting insects. We shed light on a complex of interactions influencing an important invader.